Interdependence versus Truth and Justice: Lessons from Reconciliation Processes in Maluku - Diah Kusumaningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Truth commissions and trials have been applauded as the way to move on from a violent past. Yet, some post-conflict societies managed to move toward reconciliation without the presence, or the effective presence of such formal institutions. This article discusses a number of lessons learned from Maluku, where reconciliation took the interdependence path. Taking on an interpretive, emic approach, it elaborates on the sites and mechanisms of interpendence. It argues that interdependence can be as viable as truth and justice procedures in bringing about reconciliation.